Academic Senate Minutes 2001-10-25 - Academic Senate:::::::::
Agenda and Minutes approved. Consent items, new course in Theatre Arts and 126 unit B.S. in Biology approved. Women's and Gender Studies proposal to be a department referred to EPC and APC. Hutchins/Education Blended B.A. and Teaching Credential approved. Resolution supporting Principles of a Living Wage approved. Lecturer's Compensation resolution tabled for two weeks. Financial report on the Green Music Center from Larry Furukawa-Schlereth. Report from AS President designee, Statewide Senator.